Characterization of urea encapsulated by biodegradable starch-PVA-glycerol - Lum, Yip Hing; Shaaban, Azizah; Mitan, Nona Merry Merpati; Dimin @ Mohd Amin, Mohd Fairuz; Mohamad, Noraiham; Abdul Hamid, Nor Nadiah; Se, Sian Meng (Springer, 2013)
The influence of the blending ratio of biodegradable starch/polyvinyl alcohol (PVA)/glycerol in encapsulating urea has been investigated. It is found that water absorption capacity increased approximately 135 % as the amounts of starch, PVA and glycerol in the composite film increase. Therefore, the swell ability of the composite film is increased and the urea is released from the composite film in the wet environment. The FTIR shows that the urea had been encapsulated successfully in the composite films. Moreover, the soil burial biodegradation results indicated that the biodegradability of the starch/PVA/glycerol/urea composite film strongly depended on the PVA proportion in the composite film matrix. The DSC results show that the higher the amount of PVA in the composite film, the less change of the melting enthalpy value. The crystalline region of PVA remains after biodegradation.